Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12864-019-5733-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of glyoxalase-like gene families in grape (Vitis vinifera L.) and their expression profiling in response to downy mildew infection

Abstract: Background: The glyoxalase system usually comprises two enzymes, glyoxalase I (GLYI) and glyoxalase II (GLYII). This system converts cytotoxic methylglyoxal (MG) into non-toxic D-lactate in the presence of reduced glutathione (GSH) in two enzymatic steps. Recently, a novel type of glyoxalase III (GLYIII) activity has observed in Escherichia coli that can detoxify MG into D-lactate directly, in one step, without a cofactor. Investigation of the glyoxalase enzymes of a number of plant species shows the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 74 publications
(137 reference statements)
1
23
1
Order By: Relevance
“…Glutathione is used in the first reaction catalysed by GLYI but is recycled in the second reaction catalysed by GLYII. D-lactate is further metabolized to pyruvate through Dlactate dehydrogenase (D-LDH) enzyme which passes electrons to cytochrome C (CYTc) Very recently, 4 GLYI and 2 GLYII genes encoding putative functionally active glyoxalase isoforms have also been identified in grapes [22]. Similarly, a recent comparative analysis of glyoxalases genes in Erianthus arundinaceus and a commercial sugarcane hybrid has led to the identification of 9 GLYI and 7 GLYII genes in sugarcane, with the wild cultivar showing higher expression of glyoxalase genes under stress conditions than the commercial variety [23].…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione is used in the first reaction catalysed by GLYI but is recycled in the second reaction catalysed by GLYII. D-lactate is further metabolized to pyruvate through Dlactate dehydrogenase (D-LDH) enzyme which passes electrons to cytochrome C (CYTc) Very recently, 4 GLYI and 2 GLYII genes encoding putative functionally active glyoxalase isoforms have also been identified in grapes [22]. Similarly, a recent comparative analysis of glyoxalases genes in Erianthus arundinaceus and a commercial sugarcane hybrid has led to the identification of 9 GLYI and 7 GLYII genes in sugarcane, with the wild cultivar showing higher expression of glyoxalase genes under stress conditions than the commercial variety [23].…”
Section: Introductionmentioning
confidence: 99%
“…As we have shown, VvGLYI‐4 plays important roles in P . capsici infection in tobacco and P. viticola resistance in grapevine (Li et al., 2019). We used its promoter to screen the potential targets by Y1H screening and found one transcription factor, VvNAC72 .…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study we identified several GLYI genes in the transcriptome of grapevine and found that they potentially contribute to pathogen defense. In particular, the expression of VvGLYI‐4 was strongly increased after grapevine leaves were inoculated with P. viticola (Li et al., 2019). However, how the plant defense mechanism causes VvGLYI‐4 to be highly expressed in response to downy mildew infection remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In recent study, the glyoxalase enzyme of rice not only increased tolerance abiotic stresses (salinity, drought and extreme temperatures) but also reduced damage from biotic stresses (Rhizoctonia solani) [43]. Moreover, in grape, most glyoxalase genes had two periods of high expression after downy mildew inoculation [22]. In our study, the induced genes after infection may have response on the S. sclerotiorum pathogen, e.g., BnaGLYI07, BnaGLYI24, BnaGLYI25, BnaGLYII02, BnaGLYII03, BnaGLYII18 and BnaGLYII19 genes, whose expression were signi cantly up-regulated in both cultivars.…”
Section: Different Expression Patterns Of Glyoxalase Genesmentioning
confidence: 99%
“…Moreover, GLYI and GLYII genes were present as multi-gene families. To date, genome-wide identi cation of glyoxalase family has been carried out in six plant genomes Arabidopsis thaliana, Oryza sativa, Glycine max, Medicago truncatula, Brassica rapa and Vitis vinifera L. [17,[22][23][24][25][26]. There are at least 11 GLYI homologous genes in A. thaliana and rice, twenty-four GLYI members in soybean genome, and 15 in B. rapa.…”
Section: Introductionmentioning
confidence: 99%